System of Diagnostic Indicators for Low-Productive and Degraded Soils to Assess Their Suitability for Afforestation - Lisnyak, A. A.; Torma, S.; Kulyk, M. I. (Man and Environment. Issues of Neoecology, 2023)
Purpose. The identification of soil indicators for assessing the forest growth potential of soils for the possibility of afforestation.Methods. The indicators were chosen among the soil parameters most often used to assess fertility: reserves and thickness of forest litters, morphological characteristics of soils, particle size distribution, acidity, humus and various forms of NPK content, composition and content of exchangeable cations. The research was carried out in natural medieval forests according to the methods generally accepted in forest inventory, typology, soil science, analytical work - according to classical agrochemical and standardized methods. Results. The article gives an analysis of the problem of forestry typological evaluation of low-output and degraded soils (sandy, with shortened profile, salted, eroded), which were withdrawn from agricultural usage. The actual and theoretical material on the basis of which the range of issues related to the evaluation of forest land use in different natural zones is generalized, was collected and analyzed. On the main categories of low-productive lands in different natural zones of the flat part of Ukraine temporary trial areas were laid, where soil and typological investigation were conducted. The soil indicators and parameters of forest productivity of low productivity and degraded soils are determined, on the basis of which the classification of soils based on the degree of their suitable for afforestation has been developed. The suitability of soils for afforestation were evaluated in three categories: suitable for afforestation, limitedly suitable and unsuitable suitable for afforestation.Conclusions. The experience of afforestation of low-productive and degraded soils is generalized and a system of diagnostic indicators for their forest typological evaluation on zonal and morphological basis is proposed, and an information analysis on the problem of assessing the suitability for afforestation of low-productive lands (saline, stony, sandy) that are derived from agricultural circulation is provided. The suitability of soils for afforestation is described by a system of soil indicators, in particular, their particle size distribution, humus content, common and mobile forms of NPK, and exchangeable cations. However, among these indicators, one can single out informative indicators of the level of productivity of forest lands - mineralogical (chemical) and granulometric composition of soils. At the same time, it has been proved that the granulometric composition of the soil determines such important characteristics as the content of exchange bases, common forms of phosphorus, potassium, and humus.